Seed Yield and its Attributing Characters as Influenced by Crossing Period in Hybrid Cotton DHB-290 - S.R. DODDAGOUDAR; M. SHEKHARGOUDA; B.M. KHADI; M.R. ESHANNA; N.K. BIRADARPATIL; H.M. VAMADEVAIAH (Seed Research, 2026)
The seed yield and its attributing characters, at five different crossing periods each with 15 days interval, in DHB-290 hybrid cotton showed increased number of flowers crossed, crossed bolls picked and seed yield from initial (C₁) crossing period and reached maximum at third (C3) and fourth (C₁) fortnight crossing periods, respectively. Whereas, the seed yield attributing characters such as, boll setting percentage, boll weight, seed weight per boll and seed index decreased from the initial (C₁) crossing period to the last crossing period (C5).